2019
DOI: 10.1002/jocb.406
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Experimental Research on Embodied Creativity: Revisiting the Mind–Body Connection

Abstract: A growing body of experimental work highlights the potential value of unstructured, interactive, or spontaneous motions, including gestures, dance, shifting body postures, physical object-manipulation, drawing, etc. to favorably impact creative performance. However, despite these favorable findings, to our knowledge, no systematic review has been conducted to explore the totality of evidence for embodied activities in this arena. Thus, the objective of this paper was to systematically evaluate the potential ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Studies on embodied cognition have also revealed that bodily sensation and movements can modulate divergent creative thinking [11,12]. For example, walking better facilitates subsequent divergent thinking than sitting [13], suggesting an effect of bodily movements per se on creativity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on embodied cognition have also revealed that bodily sensation and movements can modulate divergent creative thinking [11,12]. For example, walking better facilitates subsequent divergent thinking than sitting [13], suggesting an effect of bodily movements per se on creativity.…”
Section: Introductionmentioning
confidence: 99%
“…Abstract concepts represented by somatosensation and bodily movements also modulate creativity [11,12]. To understand abstract concepts, human cognitive as well as linguistic processes employ metaphors mapping abstract concepts onto superficially dissimilar concrete concepts [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…As embodied cognitive science has matured, some scholars argue that the embodied metaphor thesis is not radical, rather it is an example of grounded cognition that is compatible with CC models (Adams, 2010; Gallagher, 2015a; Shapiro, 2019). Nonetheless, a number of experimental studies examining embodiment in creativity have focused on how movement might enact embodied metaphors to enhance divergent and convergent thinking (Stanciu, 2015; Frith et al, 2019).…”
Section: A Conceptual Analysis Of Radical Embodiment In Creativitymentioning
confidence: 99%
“…The view that bodily movements shape the mind, and consequently creativity, can be interpreted within the frame of the embodied cognition theoretical approach [ 8 , 9 , 10 ]. This approach posits four basic principles: (1) the body, including brain and sensorimotor capabilities, supports cognition(embodiment) [ 11 ]; (2) organisms interact with both the physical environment on the basis of the possibilities (affordances) available [ 12 , 13 ] and the social-cultural environment (embedded) [ 14 ]; (3) cognition is for action, that is organisms form their experiences by initiating actions while interacting with their environment (enactive) [ 8 , 15 , 16 , 17 ]; (4) cognition is distributed beyond the body, that is non-biological devices (e.g., computers, smartphone, etc.)…”
Section: Introductionmentioning
confidence: 99%